Planning of Conventional Air Emission Reduction Strategy from the Transportation, Domestic, and Solid Waste Sector in Salatiga City - Budi Prasetyo Samadikun; Nurandani Hardyanti; Dea Wijayanti; Zumrotus Sa'adah (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
In 2020 Salatiga City has a population of 192,322 people with a population growth rate of 1.18%. The increase in population causes an increase in consumption needs, waste generation, and the number of vehicles due to increased population mobility. The purpose of this plan is to take an inventory of conventional air emissions in the transportation, domestic, and waste sectors and to plan strategies to reduce conventional air emissions in Salatiga City. The transportation sector emissions inventory is calculated using the Tier 2 method, while the domestic and solid waste sectors are calculated by multiplying activity data by emission factors. In the calculation of the capacity, the box model method is used and the SWOT analysis is used to determine the emission control strategy. The results of the inventory of conventional air emissions in the transportation sector for SOx are 121.06 tons/year, NOx is 2,615.51 tons/year, CO is 18,040.89 tons/year, and PM10 is 299.66 tons/year. Meanwhile for the domestic sector, SOx is 0 kg/year, NOx is 14,755.53 kg/year, CO is 4,070.86 kg/year, and PM10 is 190,326 kg/year. Then from the solid waste sector, SOx emissions were 3,653,071.85 g/year, NOx was 21,918,429.85 g/year, CO was 306,858.017.94 g/year, and PM10 was 219,184,298.53 g/year. . The results of the capacity calculation show that the City of Salatiga can still accommodate conventional air emissions for SOx, NOx, CO, and PM10. However, a reduction strategy is still needed to control air pollution. The strategic plan used is an increase in green open space by 20%, the development of an Intelligent Transportation System, emission testing of private vehicles, the substitution of LPG with biogas from organic waste and livestock manure, as well as community development for waste reduction and optimization of waste facilities.